Vitamin D Status in Early Childhood and Neurodevelopment and Growth at Age 6–9 Years in North India (P11-061-19). (13th June 2019) - Chowdhury, Ranadip; Taneja, Sunita; Kvestad, Ingrid; Hysing, Mari; Bhandari, Nita; Strand, Tor
Abstract: Objectives: The extent to which vitamin-D deficiency (< 10 ng/ml) is associated with neurodevelopment and linear growth in middle childhood. Methods: The study is a follow-up of a factorial randomized double-blind placebo-controlled trial in 1000 North Indian children 6 to 30 months at enrolment, receiving daily 2 RDAs of vitamin B12 and/or folic acid or placebo for 6 months. When the children were 6–9 years old, we included 791 for cognitive assessments with the Wechsler Intelligence Scale for Children, 4 th edition INDIA (WISC-IV), Crichton Verbal Scale (CVS), NEPSY-II and BRIEF 2 and linear growth. Multiple logistic and linear regressions were used to examine the association between vitamin-D deficiency at baseline and neurodevelopment and growth in middle childhood. Results: Among the 791 children who consented to participate, baseline Vitamin D status was available for 716 children who were included in this analysis. Of these, 251 (35.1%) were vitamin-D deficient (< 10 ng/ml). There were no significant differences in any of the cognitive outcomes between vitamin-D deficient and non-deficient children. Also, we did not find any association between linear growth at follow up and vitamin D deficiency at baseline. Conclusions: The results from this analysis do not support that vitamin-D deficiency in early childhood is important for growth and neurodevelopment in middle childhood. Funding Sources: Thrasher Research Fund; The Research Council of Norway. Supporting Tables, Images and/or Graphs: